2011
DOI: 10.1037/a0022473
|View full text |Cite
|
Sign up to set email alerts
|

Error discounting in probabilistic category learning.

Abstract: Some current theories of probabilistic categorization assume that people gradually attenuate their learning in response to unavoidable error. However, existing evidence for this error discounting is sparse and open to alternative interpretations. We report two probabilistic-categorization experiments that investigated error discounting by shifting feedback probabilities to new values after different amounts of training. In both experiments, responding gradually became less responsive to errors, and learning wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 60 publications
1
24
1
Order By: Relevance
“…For each stimulus, the average choice probability is more extreme than the feedback probability associated with that stimulus. This overshooting behavior is typical of responding under probabilistic feedback (e.g., Craig et al, 2011;Nosofsky & Stanton, 2005;Sewell et al, 2018;Shanks et al, 2002). Visual inspection of the individual response profiles confirmed that all participants exhibited the same probability matching behavior, responding similarly to each stimulus over the entire course of learning.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…For each stimulus, the average choice probability is more extreme than the feedback probability associated with that stimulus. This overshooting behavior is typical of responding under probabilistic feedback (e.g., Craig et al, 2011;Nosofsky & Stanton, 2005;Sewell et al, 2018;Shanks et al, 2002). Visual inspection of the individual response profiles confirmed that all participants exhibited the same probability matching behavior, responding similarly to each stimulus over the entire course of learning.…”
Section: Resultsmentioning
confidence: 63%
“…Each cue is paired with a unique feedback probability, which determines the relative frequency with which the cue is paired with a Category A or Category B outcome during learning. In tasks using a small number of nonconfusable cues, performance typically stabilizes after each cue has been presented around 30-40 times (e.g., Craig, Lewandowsky, & Little, 2011;Sewell et al, 2018). Because learning proceeds rapidly, it is possible for people to complete multiple runs through the learning task within a single experimental session.…”
Section: Probabilistic Category Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Error discounting is when people slow down their rate of learning in order to account for a certain amount of errors (Craig, Lewandowsky, & Little, 2011). In both of the experiments by Craig et al, participants had to categorize four items into two categories (A and B) on a probabilistic basis (items belonging to category A changed periodically from probabilities of .8 to .6 to .4).…”
Section: Discussionmentioning
confidence: 99%